If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 115 = 10(x + 60) + 65 Reorder the terms: 115 = 10(60 + x) + 65 115 = (60 * 10 + x * 10) + 65 115 = (600 + 10x) + 65 Reorder the terms: 115 = 600 + 65 + 10x Combine like terms: 600 + 65 = 665 115 = 665 + 10x Solving 115 = 665 + 10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-10x' to each side of the equation. 115 + -10x = 665 + 10x + -10x Combine like terms: 10x + -10x = 0 115 + -10x = 665 + 0 115 + -10x = 665 Add '-115' to each side of the equation. 115 + -115 + -10x = 665 + -115 Combine like terms: 115 + -115 = 0 0 + -10x = 665 + -115 -10x = 665 + -115 Combine like terms: 665 + -115 = 550 -10x = 550 Divide each side by '-10'. x = -55 Simplifying x = -55
| 30x^6+33x^5+9x^4=0 | | X-8=72-4x | | =x^4-8 | | -5-4x=3x+24 | | 2x-16=-6x-8 | | -6-(6-12x)=4x-2(x+11) | | -3(p+4)-2(1-8p)=3(4+2p) | | x+(x+2)=90 | | 5p-7q=8 | | 1/4x-4=-11 | | 84/s= | | 5p+-105=p | | -5(r+9)=-66 | | 9w+3=3(3w+1) | | 2(n/6+22)=60 | | 3.4/0.2= | | 8(x+7)+11=10x-2(x-6) | | 12m^2+40m-32=0 | | 3x^2+5=-80 | | 3x+5+8x-4= | | 7x(h-10)= | | 4+(-20)+20= | | x+22x=90 | | 4(9c+7)= | | 29=-3x-16 | | (-1.75)(-4)= | | 6(y+x)= | | 10x+9=30+10x-21 | | 2a-5/7=3 | | 1/5*7/3 | | -2x-33=-6x-9-8x | | 2(7c-1)-8=12c+2 |